Ex ante welfare analysis of technological change: The case of nitrogen efficient maize for African soils - Kostandini, Genti; La Rovere, Roberto; Guo, Zhe (Wiley, 2016)
This study evaluates the potential impacts of the Improved Maize for African Soils (IMAS) project in two countries of Africa: Kenya and South Africa. The IMAS varieties offer significant yield advantages for regions where low or no fertilizer is used. The analysis uses spatial production data and household data to account for the level of fertilizer use in different agroecological zones of the country as well as different types of maize producing households. Results suggest that IMAS will deliver a total of US$586 million in gross benefits with US$136 million and US$100 million of benefits to producers in Kenya and South Africa, respectively, and an additional US$112 million to consumers in Kenya and US$238 million to consumers in South Africa. These benefits could help more than 1 million people escape poverty in the two countries by 2025. Household level results suggest that small households in areas with relatively low levels of fertilizer use stand to gain significant benefits.